Optimalisasi Hasil Belajar Siswa melalui Kinerja Guru dan Kualitas Sarana Prasarana di SDN Rawa Buntu 01 - Waliyudin, Muhammad Fatih; Fadiyah, Nur; Azzahra, Sabrina Nisa (Tadris: Jurnal Manajemen Pendidikan Islam, 2026)
This study aims to determine the influence of teacher performance and the quality of facilities and infrastructure on the mathematics learning outcomes of sixth-grade students at SDN Rawa Buntu 01. The background of this research is based on the phenomenon of low student learning achievement, which is suspected to be influenced by internal factors (teacher performance) and external factors (facilities and infrastructure). The method used is a quantitative method with an associative approach. The research sample consisted of 30 sixth-grade students selected using a saturated sampling technique. Data collection techniques involved questionnaires and documentation. Data analysis was conducted using multiple linear regression and hypothesis testing (t-test and F-test) with the help of SPSS. The results of the study show that partially, teacher performance does not have a significant effect on student learning outcomes, as indicated by a significance value of 0.408 > 0.05. However, the quality of facilities and infrastructure significantly affects student learning outcomes, with a significance value of 0.001 < 0.05. Simultaneously, teacher performance and the quality of facilities and infrastructure significantly influence students’ mathematics learning outcomes, as indicated by an F-value of 26.580 > F-table value of 3.340 and a significance value of 0.001 < 0.05. The resulting regression equation is Y = 22.543 – 0.073 X₁ + 0.465 X₂ + e, which shows that an increase in the quality of facilities and infrastructure will improve student learning outcomes, while teacher performance in this study did not show a significant independent effect. This study concludes that successful learning is not only determined by the teacher but is also strongly influenced by adequate learning facilities and infrastructure. Therefore, schools need to pay attention to the management of learning facilities while continuing to encourage the improvement of teacher competencies to create an optimal learning process and maximize learning outcomes.